Postoperative Quality of Life after Open Transinguinal Preperitoneal Inguinal Hernia Repair Using Memory Ring or Three-dimensional Devices. Issue 8 (August 2013) - Williams, Kristopher B.; Bradley, Joel F.; Wormer, Blair A.; Zemlyak, Allay; Walters, Amanda L.; Colavita, Paul D.; Lincourt, Amy E.; Tsirline, Victor B.; Belyansky, Igor; Heniford, B. Todd
A transinguinal preperitoneal (TIPP) approach has become a common technique for inguinal hernia repair. Our goal was to compare the impact of the two mesh designs for this operation: a flat mesh with a memory ring device (MRD) or a three-dimensional device (3DD) containing both onlay and preperitoneal mesh components. The prospective International Hernia Mesh Registry (2007 to 2012) was queried for MRD and 3DD inguinal hernia repairs. Outcomes and patient quality of life (QOL), using the Carolinas Comfort Scale (CCS), were examined at 1, 6, 12, and 24 months. Standard statistical methods were used, and multivariate logistic regression was performed using a forward stepwise selection method. TIPP was performed in 956 patients. Their average age 57.4 ± 15.3 years, 94.0 per cent were male, and mean body mass index was 25.7 ± 3.2 kg/m 2 . MRD was used in 131 and 3DD in 825. Follow-up was 97, 82, 87, and 80 per cent at 1, 6, 12, and 24 months, respectively. Complications were not significantly different ( P > 0.05). Recurrence was 0.8 per cent for MRD and 2.1 per cent for 3DD ( P = 0.45). Comparing patient outcomes of MRD with 3DD at 1 month, 18.9 versus 11.5 per cent had symptoms of mesh sensation ( P = 0.02); 28.7 versus 14.8 per cent had movement limitations ( P < 0.01). MRD use was a significant independent predictor of movement limitation (odds ratio, 2.3; confidence interval, 1.4 to 3.7). No significant differences in CCS scores were seen at 6, 12, and 24 months. TIPP repair is safe and has a low recurrence rate. Early postoperative QOL is significantly improved with a 3DD mesh compared with MRD.